(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
The study investigated the skin temperature (T_sk) at sixteen points, Stratum Corneum Water Content (SCWC) and TransepidermalWater Loss (TEWL) at fourteen points over the ventral and dorsal surfaces, during submaximal cycling exercise in an ambient temperature of 25 °C, and a relative humidity of 60%. Nine healthy competitive males completed a 20 min rest on the cycle and 5-min warm-up, followed by a 30 min of cycle exercise at 70% maximal heart rate and 30 min recovery. Average mechanical power output and pedaling rate were 150 W and 70 rpm. The results showed that the ventral and dorsal skin temperatures were significantly decreased from a minimum of 0.68 °C up to 3.48 °C than those measured at rest before cycling. In accordance with the regions of declines in skin temperatures, the values of SCWC and TEWL almost attained 120 A.C.U. and 40 ∼ 60 g ⁄ h.m². Meanwhile, the subjects produced 0.45 L ⁄ h sweating throughout the experiment. The distribution state of Tsk, SCWC and TEWL could be visualized directly by a novel color mapping of human body. The results obtained suggest that during the submaximal cycling exercise, the reduction of skin surface temperature is associated with the evaporative heat loss due to skin sweat.